Emerging role of SMYD family of proteins in human tumorigenesis - Bibi, Afshan; Sarfraz, Ayesha; Sajjad, Amna; Sarfraz, Iqra; Munawwar, Aasma; Zarbab, Aneeqa; Sattar, Mehran; Rasul, Azhar (Universiti Kebangsaan Malaysia, 2023)
Protein lysine methylation is a post-translational modification (PTM) that promotes protein complex formation to regulate DNA replication, gene expression, and repair mechanisms. The Su(Var)3–9, Enhancer-of-zeste and Trithorax (SET) and Myeloid, Nervy, and DEAF-1 (MYND) domain-containing proteins SMYD are lysine methyltransferases that catalyze the methylation of various histone and non-histone proteins. There are five members of this SMYD family, and all of these have conserved SET and MYND domains. The SET domain is divided into two segments by the MYND domain (the S-sequence and a core SET domain). SMYD Family performs a key role in numerous biological functions, including growth, development, apoptosis, and proliferation. SMYD family members are associated with skeletal and cardiac muscle physiology and pathology. Several studies have shown that aberrant lysine methylation plays a significant role in oncogenesis. Recently, the SMYD family has gained importance for its role in various mechanisms involved in cancer development and progressions, such as methylation and modification of tumor suppressor proteins (p53 and pRb), transcriptional factors (STAT3, NF-κB), nuclear proteins (PARP1), chaperons (Hsp90), protein kinases (MAPK, ERK), and cell cycle regulatory proteins (CDKN2). SMYD family proteins drive oncogenesis, lead the way to metastasis, and develop chemoresistance, allowing cancer cells to grow, invade the neighboring tissues, and resist therapeutics. In this review, we summarize SMYD family members’ role in different cancers by focusing on their histone and non-histone methylation targets and illustrating the mechanism of SMYD family-mediated oncogenesis.